2012
DOI: 10.1537/ase.1107312
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of mortality profiles from non-adult human skeletons in Edo-period Japan

Abstract: Reconstruction of the mortality profiles of non-adult human skeletons from an archeological site should greatly assist the interpretation of the sanitation, health, disease, and behavior of past human populations. The purposes of this study are to examine non-adult skeletons from the Sakaikango-toshi 871 (SKT 871) site in Edo-period (17-19th centuries AD) Japan, to estimate their age-atdeath distribution, and to discuss whether paleodemographic estimates can yield appropriate mortality patterns of this sample.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…In archaeology, this reflects perceptions of childhood agency. Mortality profiles for archaeological hunter-gather samples corroborate a bimodal pattern with mortality peaking during the earliest years and then again at a later stage in life (Angel, 1969;Owsley and Bass, 1979;Mensforth, 1990;Nagaoka et al, 2012;Flensborg et al, 2013). However, research on living communities suggests that children are essential to understanding kin and social structure in prehistoric contexts.…”
mentioning
confidence: 77%
“…In archaeology, this reflects perceptions of childhood agency. Mortality profiles for archaeological hunter-gather samples corroborate a bimodal pattern with mortality peaking during the earliest years and then again at a later stage in life (Angel, 1969;Owsley and Bass, 1979;Mensforth, 1990;Nagaoka et al, 2012;Flensborg et al, 2013). However, research on living communities suggests that children are essential to understanding kin and social structure in prehistoric contexts.…”
mentioning
confidence: 77%
“…The contingency tables of age and Buckberry and Chamberlain's auricular surface stage for Japanese reference samples (Nagaoka et al, 2012b) were used to calculate the posterior probability of being a particular age conditional on being in a particular state of an age indicator. The prior probabilities used in the calculation are uniform ones, where an equal prior probability is assigned to each age category, because in this assumption the estimated age-at-death distribution of the target sample is independent of that of the reference one (Nagaoka et al, 2012a).…”
Section: Methodsmentioning
confidence: 99%
“…The age‐at‐death distribution of this entire population indicates that the peak was the foetal stage and that the number of deaths decreased with age (Nagaoka et al, ). A concentration at full gestation term implies that deaths in this sample are related to birth, consistent with natural mortality (Nagaoka et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Most studies on Japanese Edo skeletons have revealed secular trends (Nakahashi, ; Suzuki, ) and regional and socioeconomic differences (Nagaoka, ; Suzuki, ) through craniometric traits. Recent advances in bioarchaeology have involved the studies of dental caries (Oyamada et al, ), linear enamel hypoplasia (Nakayama, ), paleodemography (Nagaoka, Abe, & Shimatani, ), and stable isotope analyses (Tsutaya, Nagaoka, Sawada, Hirata, & Yoneda, , ; Yoneda et al, ) of Edo period remains. These multidisciplinary studies indicate that social classes, regions, and chronological ages played an important role in intrapopulation and interpopulation variation in these bioarchaeological markers.…”
Section: Bioarchaeology Of the Japanese Edo Periodmentioning
confidence: 99%
See 1 more Smart Citation